2016
DOI: 10.1017/s0007114516002877
|View full text |Cite
|
Sign up to set email alerts
|

The effect of healthy dietary consumption on executive cognitive functioning in children and adolescents: a systematic review

Abstract: A systematic review was conducted to evaluate whether healthier dietary consumption among children and adolescents impacts executive functioning. PubMed, Education Resources Information Center, PsychINFO and Thomson Reuters' Web of Science databases were searched, and studies of executive functioning among children or adolescents aged 6-18 years, which examined food quality, macronutrients and/or foods, were included. Study quality was also assessed. In all, twenty-one studies met inclusion criteria. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 40 publications
(102 reference statements)
2
62
0
1
Order By: Relevance
“…The cross-sectional analyses in the present study suggesting that there is an association between TN and fatty fish intake, and a healthier dietary pattern is interesting. Other studies in healthy young participants have reported associations between cognitive outcomes and fish intake [ 13 , 15 ] and between a healthy diet or intake of healthy foods [ 37 – 40 ]. However, because the present results are based on cross-sectional analyses, we cannot make statements on causality; although it is tempting to make the interpretation that TN was driven by the diet measures, the opposite may be true, such that higher scores in TN may implicate better dietary choices.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional analyses in the present study suggesting that there is an association between TN and fatty fish intake, and a healthier dietary pattern is interesting. Other studies in healthy young participants have reported associations between cognitive outcomes and fish intake [ 13 , 15 ] and between a healthy diet or intake of healthy foods [ 37 – 40 ]. However, because the present results are based on cross-sectional analyses, we cannot make statements on causality; although it is tempting to make the interpretation that TN was driven by the diet measures, the opposite may be true, such that higher scores in TN may implicate better dietary choices.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrients in fruits and vegetables are critical for proper growth and development (1)(2)(3) , cognitive function (4) and chronic disease prevention (5)(6)(7)(8)(9) . Unfortunately, children living in the USA consume fewer servings than recommended, particularly those living in low-income households (10)(11)(12) .…”
mentioning
confidence: 99%
“…Traditional, dietary patterns (exemplified by the Mediterranean diet) have been associated with good emotional and cognitive health, as well as lowered risk of depression and attention deficit hyperactivity disorder [65][66][67]. On the other hand, greater adherence to the westernized diet is associated with a smaller hippocampus, the area of the brain crucial to aspects of memory [68].…”
Section: Nutrition For Mental Cognitive Healthmentioning
confidence: 99%